The dynamics of cytolytic syndrome parameters in the period of late manifestations of cranioskeletal trauma in case of concomitant chronic hepatitits and the effectiveness of armadine correction - Prokhorenko, O. (Journal of Education, Health and Sport, 2021)
Relevance. Cranioskeletal trauma has the most severe lesions and is accompanied by significant mortality. The impact of comorbidities caused by the cardiovascular system, in particular diffuse lesions of internal organs are not fully investigated under this condition. A common mechanism of pathogenesis of these pathological processes is the development of cytolytic syndrome. Goal of study: is to determine the dynamics of markers of cytolysis in the period of late manifestations of cranioskeletal trauma in conditions of concomitant chronic hepatitis and to evaluate the effectiveness of armadine correction. Materials and methods. Cranioskeletal trauma, chronic hepatitis, and its combinations were modelled in separate groups of nonlinear white male rats. Armadine at a dose of 20 mg/kg intraperitoneally was used to correct the group with combined lesions. The activity of alanine and aspartate aminotransferases was determined in the serum of experimental animals on 14, 21, 28 and 35 days after injury. Results and its discussion. The application of cranioskeletal trauma in the late manifestations of traumatic disease is accompanied by increased cytolysis. The activity of alanine and ampartate aminotransferase in the serum of injured animals is increased after 14 days of the post-traumatic period and continues to increase up to 21 days with a subsequent decrease. Moreover, up to 35 days only the activity of aspartate aminotransferase reaches the level of control, while the activity of alanine aminotransferase continues to remain significantly higher. The use of armadin under these conditions from the 21st day of the experiment causes a decrease in the changes of the studied parameters compared with the group of animals without correction. Conclusions. The application of cranioskeletal trauma on the background of chronic hepatitis in the late manifestations of traumatic disease is accompanied by a greater change of cytolysis than in the group of injured animals without concomitant liver damage. The use of armadine causes a statistically significant decrease in the intensity of the detected disorders, starting from 21 days of the experiment.